IS CLEISTOSPERMY AND COENOSPERMY RELATED TO SPERM TRANSFER? A COMPARATIVE STUDY OF THE MALE REPRODUCTIVE SYSTEM OF PACHYGRAPSUS TRANSVERSUS AND PACHYGRAPSUS GRACILIS (BRACHYURA: GRAPSIDAE) - Tiseo, Gisele R. [UNESP]; Mantelatto, Fernando L.; Zara, Fernando J. [UNESP] (Crustacean Soc, 2014)
We describe the production of spermatophores and the seminal fluid in Pachygrapsus transversus and P. gracilis. Both species have tubular testes. The vas deferens is divided into anterior (AVD), middle (MVD), and posterior (PVD). The AVD in P transversus is further divided into two portions: proximal without spermatophores and distal filled with coenospermic spermatophores. In P gracilis, the AVD was not divided because spermatophores were in cleistospermia. In both species, the MVD is responsible for producing part of the seminal fluid reactive polysaccharides. The accessory gland opens into the PVD and changes the characteristics of the seminal fluid. The glandular secretion is glycoproteinaceous in P transversus and rich in acidic and neutral polysaccharides in P gracilis. The eggs of P. transversus are larger than those of P. gracilis. The differences in spermatophore structure and the characteristics of seminal fluid seem to indicate physiological differences related to sperm transfer.
Keywords: histochemistry; histology; male reproductive system; seminal fluid spermatophore